CHALLENGES TO GREEN SPACES IN MODERN CITIES - Veselin Rangelov; Alexander Pregyov (World Science, 2023)
Accelerated rates of urbanization suggest that by 2050, more than 70% of the world’s population will live in megacities. The rapid migration to big cities and the impossibility of endless expansion of their physical boundaries, necessitate the search for new solutions, both for housing and for accompanying infrastructure. Green areas are no exception, especially since they are among the elements of the urban environment that are standardized in terms of quantity and quality, and from them, to a large extent, we judge the quality of life. All this necessitates a rethinking of established standards and a search for new opportunities to provide the necessary green spaces for every resident.